On the Notion of Developmental Computing Machine - Costa, Antônio Carlos da Rocha; Dimuro, Graçaliz Pereira (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2007: Anais do XXXIV Seminário Integrado de Software e Hardware, 2007)
A developmental machine is a machine that is able to increase its structure and functionality as it operates in interaction with its environment. This paper initially explains the importance that the notion of machine development may have for Computer Science. Next, it attempts to identify the main reasons why the research community that is keen to the foundational issues lacks a serious concern with such issue. Then, it presents some fundamental problems that apparently have to be tackled by any approach to the notion of developmental computing machine. Finally, the paper introduces the initial elements of the domain-theoretic model of machine development that we are constructing.